Formação de professoras dos anos iniciais do ensino fundamental em Iguatu-CE: desafios da construção do pertencimento afro através da pretagogia - Félix, Cristiane de Oliveira (2021)
Starting from the understanding that there is racism in the school environment; and that the school can contribute directly or indirectly to the reproduction of racist practices, I understand that in return this should be a space for transformation and combat this big social problem, developing an Anti-racist Education. This educational practice was constituted by the tireless struggles of the Black Social Movements in the search to exercise an education that favors the discussions on ethnic relations in Brazil, which has been possible through the legal apparatus of Law 10,639/03. Despite the advances achieved with the 10,639/03 and the fact that many researches already have as their object their applicability, it is noted that there is still an excessive delay in its execution, mainly in relation to the adequate training of teachers of Brazilian schools. The present research proposal has as its generais objective to study the possibilities and limits of strengthening the afro belonging of teachers of the initial grades of elementary school through the approach of Pretagogy. As specific objectives, I analyze the concepts that these teachers elaborate about the Fricanities before and after black interventions. For this purpose, through interventions, pedagogical actions that contribute to the construction and strengthening of Afro belonging. As references to support the research, I use the contributions of Cavalleiro (2001); Gomes (2002;2005;2017); Munanga (2005;2016); Nascimento (2017); Petit (2015;2016), among others. The research subjects were four elementary school teachers from the Padre Januário Campos Educational Center, in the city of Iguatu-Ce. The methodological proposal is inserted in the field of the qualitative approach from the research-training mediated by Pretagogy for being an afrorreferentiated theoretical-methodological contribution. The empirical approach had the presence of the Markers of Africanities for the elaboration of the formative meetings with the teachers. The work took different directions than it had been planned in the beginning and the results were even more surprising than expected. At times I felt a tone of denunciation on the part of the teachers associated with the absence of training and a concrete project on Africanities. Teachers have also come to recognize that there is racism in the environment in which they work. Making it possible for teachers to have contact with bibliographic and audiovisual materials that are not referenced, paved the way for the preparation of new anti-racist pedagogical practices.